International collaborative study for the calibration of proposed International Standards for thromboplastin, rabbit, plain, and for thromboplastin, recombinant, human, plain. (1st December 2017) - van den Besselaar, A. M. H. P.; Chantarangkul, V.; Angeloni, F.; Binder, N. B.; Byrne, M.; Dauer, R.; Gudmundsdottir, B. R.; Jespersen, J.; Kitchen, S.; Legnani, C.; Lindahl, T. L.; Manning, R. A.; et al.
Abstract : Essentials Two candidate International Standards for thromboplastin (coded RBT/16 and rTF/16) are proposed. International Sensitivity Index (ISI) of proposed standards was assessed in a 20‐centre study. The mean ISI for RBT/16 was 1.21 with a between‐centre coefficient of variation of 4.6%. The mean ISI for rTF/16 was 1.11 with a between‐centre coefficient of variation of 5.7%. Summary: Background: The availability of International Standards for thromboplastin is essential for the calibration of routine reagents and hence the calculation of the International Normalized Ratio (INR). Stocks of the current Fourth International Standards are running low. Candidate replacement materials have been prepared. This article describes the calibration of the proposed Fifth International Standards for thromboplastin, rabbit, plain (coded RBT/16) and for thromboplastin, recombinant, human, plain (coded rTF/16). Methods: An international collaborative study was carried out for the assignment of International Sensitivity Indexes (ISIs) to the candidate materials, according to the World Health Organization (WHO) guidelines for thromboplastins and plasma used to control oral anticoagulant therapy with vitamin K antagonists. Results: Results were obtained from 20 laboratories. In several cases, deviations from the ISI calibration model were observed, but the average INR deviation attributabled to the model was not greater than 10%. Only valid ISI assessments were used to calculate the mean ISI for each candidate. The mean ISI for RBT/16 was 1.21 (between‐laboratory coefficient of variation [CV]: 4.6%), and the mean ISI for rTF/16 was 1.11 (between‐laboratory CV: 5.7%). Conclusions: The between‐laboratory variation of the ISI for candidate material RBT/16 was similar to that of the Fourth International Standard (RBT/05), and the between‐laboratory variation of the ISI for candidate material rTF/16 was slightly higher than that of the Fourth International Standard (rTF/09). The candidate materials have been accepted by WHO as the Fifth International Standards for thromboplastin, rabbit plain, and thromboplastin, recombinant, human, plain.